KREATIVITAS GURU DALAM PEMBINAAN MINAT BELAJAR AL-KHOT SANTRI DI MDTA ISLAMIYAH BENGKEL - Fadhilah Maulidina; Muhammad Riduan Harahap; Dirja Hasibuan (HIBRUL ULAMA, 2025)
The objectives of this study are: 1) To find out how creative the development of Al-Khot is learning interest of students at MDTA Islamiyah Bengkel. 2) To find out what are the supporting and inhibiting factors in the process of implementing the development of Al-Khot learning interest of students at MDTA Islamiyah Bengkel. 3) To find out how the results of teacher creativity are in developing Al-Khot learning interest of students at MDTA Islamiyah Bengkel. This study was conducted in the field using a qualitative research approach, using data research techniques such as observation, interviews and documentation for data collection. Data analysis techniques involving data reduction, presentation and drawing conclusions. While the data assurance technique is in the form of data triangulation. The findings of the study are: 1) Showing that teacher creativity in fostering students' interest in learning Al-Khot is mainly seen in extracurricular activities. Although teachers have effectively utilized learning media in several subjects, they have not fully utilized supporting media in other subjects. 2) In addition, teachers have not maximized their creativity in developing interesting teaching and learning strategies. 3) However, efforts have been made to improve the learning environment by rearranging the classroom and reducing student boredom through activities such as singing. Factors that hinder teacher creativity in fostering students' interest in learning Al-Khot include the lack of school-owned learning media sources utilized by teachers, the difficulty of managing students who still have low interest in learning, so that student discipline has not been optimally directed. Meanwhile, supporting factors include teachers' interest in reading learning method books so as to increase their knowledge about creativity in teaching and teachers' activeness in participating in training on teacher creativity in teaching. The results of this study are expected to be beneficial, namely: 1) Can be used as input for educators. 2) As input for policy makers. 3) Adding to the intellectual treasury of researchers.